Unisist (1971): the feasibility of a world science information system revisited from a back to the future approach to information policy - Urbano, Cristóbal (Anuario ThinkEPI, 2024)
Review of the report published by Unesco and the International Council of Scientific Unions in 1971, in which, based on a diagnosis of the state of international access to scientific information, proposals for improvement were formulated through national and international coordination of the actors involved. Under the leadership of both organizations, a rigorous process of study of the principles, technologies and standardization of the treatment of scientific information was carried out, which fuelled a process of consultation among experts, governments and organizations, aimed at assessing the feasibility of institutionalizing a world system of scientific information. The aim of such a system was to respond to the context of information growth at the time, as well as to the requirement for international cooperation demanded by an increasingly complex science that had to be open to developing countries. The review compares the process represented by Unisist during the last quarter of the 20th century with the current reality, and points to the need to advance in the coordination of the many and diverse initiatives currently underway to improve the management of scientific information. Finally, it points to the convenience of recovering in our days the debate on information policies as a condition for such coordination.
Keywords: Unisist; Scientific information; Information policies; International cooperation; Access to information; Unesco; ICSU